Il vivente tra incarnazione e sofferenza: Spunti per un pensiero della ripetizione in Michel Henry - Pignatti, Chiara (Aisthema, 2022)
The aim of this paper is to analyze the concept of repetition within Henry's thought and to make it a key to the understanding of the process through which the living subjectivity is generated, showing how it can be useful in particular for the conception of suffering as it emerges through the Phenomenology of Life. A first part of the article will examine Henry's dynamism between the concepts of force, power and affect, and consequently investigate the peculiar movement consubstantial to Life; secondly, a genealogy of the concept of repetition will be exposed through some texts that Michel Henry dedicated to the theme of Otherness - among them, the unpublished notes of the young Henry on Schelerian intersubjectivity - and the spiritual closeness with the themes of psychoanalysis will be underlined. In the final analysis, an attempt will be made to interpret suffering in the light of repetition, distinguishing two sides of the latter that connote the affective becoming of living individuals and the dialectic of the forces that are produced in it: the immobilist, passive side of the suffering that restrains the subject, and the active and creative side of the joyful effort of reprise that allows the living being to exceed, without abandoning it, the weight that limits it.